FEED THE WORLD: WORKING TO END HUNGER IN VULNERABLE POPULATIONS - Vann, Aline (My University, 2025)
I completed my internship at Convoy of Hope, located in Springfield, Missouri. Convoy of Hope is a humanitarian, faith-based organization. Their goal, according to their website, is to “serve people who are impoverished, hungry, and hurting.” Their international initiatives include Children’s Feeding Services, Women’s Empowerment, Disaster Relief, Community Events, Agriculture, and Rural Initiatives. During my time at Convoy, I worked in the Global Programs Department which encompasses Children’s Feeding, Women’s Empowerment, and Agriculture. My assigned mentor was Melanie Morgan, R.D.N./Nutritionist. Ms. Morgan was initially the lead nutritionist for Eastern Europe, Latin America and the Caribbean, but due to a resignation during my internship, she became the only Nutritionist for the entire feeding program. She has been employed with Convoy of Hope since 2021. During my internship, I created an 8-lesson Nutrition Curriculum for Roma youth in Slovakia, assisted with a Latin American countries’ Youth Sports Initiative, drafted a Women’s Health Initiative Proposal for a group of clinics in Tanzania, and assisted in evaluating whether a garden’s produce provided sufficient calories and macros to feed a family of four for a year. I also helped calculate and analyze anthropometric data for some of the feeding centers Convoy of Hope has worldwide. I later created a project board, using Monday.com, an online platform, to provide an easy to read, high-level overview of nutrition data. I served on a Wellness Fair Planning Committee and worked during the event with my team. Finally, I presented a culminating presentation of my time at Convoy to members of the Global Programs team.
Keywords: Children's feeding program; Nutrition curriculum; Malnutrition; Sustainable agriculture; Obesity; Overweight; Ultra-processed foods; Tanzania; Women's health